2017
DOI: 10.1021/acsomega.7b01291
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Active Ionic Liquid Cholinium Dodecylbenzenesulfonate: Self-Assembling Behavior and Interaction with Cellulase

Abstract: The conventional sodium dodecylbenzenesulfonate (NaDBS) has been converted into an efficient and nontoxic anionic surface-active ionic liquid, cholinium dodecylbenzenesulfonate (Cho[DBS]). We have investigated its self-assembling behavior, interaction with the enzyme cellulase, and ecotoxicity. The surface-active properties at the air–liquid interface and the aggregation behavior of Cho[DBS] in water have been determined using tensiometry, isothermal titration calorimetry (ITC), conductometry, and dynamic ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 60 publications
1
27
0
Order By: Relevance
“…Aggregation mechanisms are usually complex and difficult to model, due to the various binding modes available for the intra and inter molecular complex formation [25,27,36]. However, any complex aggregation mechanism can be modelled as a series of sequential binding mechanism, with several steps in between the monomer and the final aggregate polymer.…”
Section: Discussionmentioning
confidence: 99%
“…Aggregation mechanisms are usually complex and difficult to model, due to the various binding modes available for the intra and inter molecular complex formation [25,27,36]. However, any complex aggregation mechanism can be modelled as a series of sequential binding mechanism, with several steps in between the monomer and the final aggregate polymer.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, they evaluated the dermal delivery of 5-fluorouracil through an IL/O system and investigated the influence of the surfactant ratio in an effort to promote their application in pharmaceutics . Recently, researchers have introduced ILs as a surface-active IL (SAIL) to serve as a surfactant by combining cations and anions with long alkyl chains for formulating different organized assemblies and improving the physico-thermal stabilities of MEs over aqueous conventional systems. , It has been reported that the SAILs possessed better surface-active properties, enhanced antimicrobial and skin permeation activity, and high temperature stability and temperature insensitivity, and they even are considered as environmentally friendly surfactants (amino acids and choline-containing SAIL) as compared to conventional surfactants. , When the nonionic conventional surfactants such as Tween-80 are used to prepare MEs, they are not stable at high temperatures as compared to ionic surfactants. , However, most of the SAILs are ionic and able to solubilize hydrophilic ILs, which facilitates the generation of stable IL/O ME formulations over a wide temperature range. , The SAILs also possess combined properties of ILs and surfactants. Recently, Zech et al formulated and characterized a SAIL-containing ME (1-hexadecyl-3-methylimidazolium chloride) where 1-butyl-3-methylimidazolium tetrafluoroborate and ethylammonium nitrate were used as polar components and dodecane was used as the nonpolar component, and Rojas et al formulated and characterized a SAIL-containing ME (1-butyl-3-methylimidazolium dodecylsulfate) composed of 1-ethyl-3-methylimidazolium ethyl sulfate as the polar medium and toluene as the nonpolar medium .…”
Section: Introductionmentioning
confidence: 99%
“…Aggregation mechanisms are usually complex and difficult to model, due to the various binding modes available for the intra and inter molecular complex formation [24,26,35]. However, any complex aggregation mechanism can be modelled as a series of sequential binding mechanism, with several steps in between the monomer and the final aggregate polymer.…”
Section: Discussionmentioning
confidence: 99%